Fatty Liver and Insulin Resistance in the Liver-Specific Knockout Mice of Mitogen Inducible Gene-6 - Byung Kil Park; Eun-Ah Lee; Hee-Youn Kim; Jun Choul Lee; Koon Soon Kim; Won Hoon Jeong; Ki Young Kim; Bon Jeong Ku; Sang Dal Rhee (Journal of Diabetes Research)
Mitogen inducible gene-6 (Mig-6) is a feedback inhibitor of epidermal growth factor receptor (EGFR) signaling pathway. The liver-specific knockout mice of the Mig-6 gene (Mig-6d/d) showed hepatomegaly and increased hypercholesterolemia. In this study, the biomarkers of insulin resistance and the effects of high-fat diets in the wild (Mig-6f/f) and Mig-6d/d mice were analyzed. The fasting plasma concentrations of glucose, triglyceride, cholesterols, free fatty acids, and HOMA-IR were measured and the glucose tolerance and insulin resistance tests were performed in the 25-week-old Mig-6f/f and the Mig-6d/d mice. The protein levels of active insulin receptor, glucose 6-phosphatase, and phosphoenolpyruvate carboxykinase were analyzed in the liver and fat. The fasting plasma cholesterol and glucose concentration were higher in the Mig-6d/d mice than the Mig-6f/f mice with increased fat deposition in the liver. But the Mig-6d/d mice had the improved glucose intolerance and insulin resistance without increased amount of phosphoinsulin receptor after insulin infusion in the liver. The hepatic concentration of phosphoenolpyruvate carboxykinase was increased in fasting Mig-6d/d mice. The feeding of high-fat diet accelerated the plasma lipids profiles and HOMA-IR in the Mig-6d/d mice but had no differential effects in oral glucose tolerance test and insulin tolerance test in both genotypes. These results suggest that the activated EGFR signaling might increase the fasting plasma glucose concentration through inducing the hepatic steatosis and the improved whole-body insulin resistance in the KO mice be caused by decreased adipogenesis in fat tissues.